Economics : a new introduction. - Stretton, Hugh (Pluto, 1999)
Stretton's introductory level economics textbook provides a much-needed alternative to standard student texts. He argues that neoclassical economic theory is inadequate, and draws on elements of Keynesian, green and feminist thought.